The Tyranny of Distance: The Treatment and Prevention of Diphtheria in Middle Canada, 1894-1920. (11th June 2022) - Rushton, Alan R
Abstract: Before 1900, diphtheria was a deadly infection in Canadian children. Clinical trials in Europe demonstrated that "antitoxin" decreased mortality of the disease. Canadian physicians first utilized the new medication in 1894 and found it most efficacious when administered early in the illness. Two factors hindered the widespread application of the new medication. Imported antitoxin was expensive, and physicians frequently purchased it themselves rather than let their patients expire. In 1916, Connaught Laboratories in Toronto began domestic production of antitoxin, and provincial governments eventually provided access to the life-saving medication for all citizens. The vast distances between families and physicians in rural districts also made it impossible to access the antitoxin before sick children were beyond hope. During the 1920s, a public health program began to actually prevent diphtheria. Ten years of experience in many regions demonstrated the efficacy of immunization as mortality from diphtheria declined to almost zero.